Nickel-substituted Lithium-Zinc-Manganese Ferritefor the Suppression of Radiated Emission Noise - Joshi, N. C.; Verma, Anjali; Kumar, Nitendar; O.B, Satheesh Kumar; Islam, S. S. (Defence Science Journal, 2007)
Nickel-substituted lithium-zinc-manganese ferrite of the composition, Li0.25-x/4 Zn0.5-x/2NixMn 0.1Fe2.15-x/4O4 where x = 0, 0.1, 0.2, 0.3, 0.4, 0.5 have been investigated for electromagnetic interference(EMI) suppression to meet the EMI standards. Various compositions were prepared by theconventional ceramic technique using mixed oxides. The ferrites were characterised for theirstructural, electrical, and magnetic, properties. The ferrites were found to posses high saturationmagnetisation, permeability, Curie temperature and resistivity, which are the desirablecharacteristics for noise-suppression application. The operating frequency of the ferrite rangedfrom 1 MHz–700 MHz, which is high enough for absorbing the electrical fast transients andradiated emission noise suppression as shown for three devices–currency counting machine,energy meter and dc-dc converter where the radiated emission noise is suppressed from 10 dBto 20 dB. In energy meter where the electrical fast transients (EFTs) are suppressed up to 5.5kV, 4.5 kV, 3.5 kV, 2.8 kV, 1.6 kV, and 1.2 kV with composition x = 0, 0.1, 0.2, 0.3, 0.4, 0.5, respectively.This material has tremendous scope of application in military equipment to comply the EMIrequirements of the military standards.